Optimasi Biaya Transportasi Pengumpulan dan Pengangkutan Susu Sapi Perah dengan Model Simulasi - , Supriyanto; , Ida Nursanti, ST., M.Eng.Sc (2017)
Collection and transport of dairy cattle breeders village of Singosari to KUD Boyolali, a logistics activities undertaken in the village milk collectors Singosari, District Mojosongo, Boyolali. The purpose of the study is to minimize the cost of transportation of the collection and transport of dairy cattle using a simulation model. Activities were carried out 2 times the collection and transport in one day by 6 trucks types of col-t with the number of 63 posts from 4 District in the town of Boyolali. Completion of the collection and transport of dairy cattle in minimizing transportation costs using the Software Arena 10.0 simulation model. The results of the research are the two best alternative to minimize transportation costs, the first reduction in truck and merging several posts in the system, the second route changes made from the alternate one. Results Alternative 1 Fixed Cost Rp. 9.000.000 and Variable Cost Rp.608.662 the costs of Rp. 9.608.662 in one week then the alternative one can save the cost of Rp. 1.885.880. Results alternative 2 Fixed Cost 9.000.000 and Variable Cost Rp. 594.860. So in one week can save the cost of Rp. 1.889.682. The selected alternative second alternative because in one week can save the cost of Rp. 1.889.682.